How do you write a polynomial with zeros: 2, 4 + sqrt5, 4-sqrt5?

1 Answer
Feb 9, 2016

x^4-14x^3+67x^2-130x+88x414x3+67x2130x+88

Explanation:

Note that: if aa is a zero of a polynomial, then (x-a)(xa) is a root of the polynomial. Applying this to the zeros at hand, we see that that polynomial is equal to

(x-2)(x-4)(x-(4+sqrt5))(x-(4-sqrt5))(x2)(x4)(x(4+5))(x(45))

We can simplify the first two through distributing. We will get to the second two, which is the more challenging part of this problem, but first distribute the minus sign.

=(x^2-6x+8)(x-4-sqrt5)(x-4+sqrt5)=(x26x+8)(x45)(x4+5)

=(x^2-6x+8)((x-4)-sqrt5)((x-4)+sqrt5)=(x26x+8)((x4)5)((x4)+5)

Notice that the last two terms are in the form (a-b)(a+b)(ab)(a+b), which equals a^2-b^2a2b2. Here, a=x-4a=x4 and b=sqrt5b=5. This gives us

=(x^2-6x+8)((x-4)^2-5)=(x26x+8)((x4)25)

=(x^2-6x+8)(x^2-8x+16-5)=(x26x+8)(x28x+165)

=(x^2-6x+8)(x^2-8x+11)=(x26x+8)(x28x+11)

Now, we can distribute these terms. There will be a lot, so hang on tight.

=overbrace(x^4-6x^3+8x^2)^((x^2-6x+8) * x^2)+overbrace(-8x^3+48x^2-64x)^((x^2-6x+8) * -8x)+overbrace(11x^2-66x+88)^((x^2-6x+8) * 11)

Combining all the like terms x^3 with x^3, and so on, our result is

=x^4-14x^3+67x^2-130x+88

Note that this polynomial can be multiplied by any constant, and the roots will be the same. However, this is the simplest form of the polynomial.